The optimization of MmNi5−xAlx hydrogen storage alloy for sea or lagoon navigation and transportation. (24th August 2016) - Molinas, B.; Pontarollo, A.; Scapin, M.; Peretti, H.; Melnichuk, M.; Corso, H.; Aurora, A.; Mirabile Gattia, D.; Montone, A.
Abstract: Among hydrogen storage materials, the MmNi5 (Mm = mischmetal, a mixture of rare earth elements) family of alloys has good properties for transportation technologies due to their ability to react reversibly with hydrogen at moderate pressures and temperatures. It is also known that different composition of Mm or partial substitution of Ni by other elements modifies the hydride stability and induces a wide range of plateau pressures, giving them an excellent versatility. This work investigates a set of MmNi5−x Alx materials exploring different kinds of Mm and Al content (x = 0.15, 0.20, 0.25), in order to determine which composition best satisfies specific working conditions for possible employment in transportation by sea or lagoon where the water of the lagoon is used as a coolant. In the specific case of a public transportation ship (the classical "vaporetto") on the Venice Lagoon, hard restrictions are required for these conditions since hydrogen sorption pressures are a key factor when considering the lagoon average temperature variations between winter and summer seasons. Experimental results of the present study led to a map of Vant'Hoff that let select the best material according to the required conditions. Highlights: Optimization of MmNi5- x Alx hydrogen storage alloy. Working conditions for employment in transportation by sea or lagoon using water of the lagoon as coolant. The materials obtained with suitable modified thermodynamic properties, can be used as hydrogen storage material in tanks on boats sailing on lagoon or sea to use sea's water to thermostat the tank.